Approximations of scientific production in health sciences in the information science in Brazil - Rene Faustino Gabriel Junior (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2021)
The work presented in this article analyzed the approximations of scientific production in health sciences in the area of information science in Brazil based on articles indexed by the Base de Dados Referenciais de Artigos de Periódicos em Ciência da Informação (Brapci) from 1972 to 2020. After searching the term ‘health’, the data were organized to in order to identify the most productive authors; to describe the forms of coauthorship; to investigate the characteristics of the journals used for publication; and to analyze the themes identified by means of the keywords. 1,293 documents were collected and after cleaning the total came to 1,140 records that were visualized using the VOSviewer software. It was verified that 3.3% of the documents concerning information science which was indexed in the database address some issue of health field. The Reciis – Revista Eletrônica de Comunicação, Informação e Inovação em Saúde (Electronic journal of communication, information and innovation in health) published 43.2% of all works obtained and has revealed a prevalence of multiple authorship.